Implementasi Aplikasi Pelayanan Warga Berbasis Android Berbasis User Centered Design - Rasiban Rasiban; Dadang Iskandar Mulyana; Sri Lestari; Muhammad Fakhri Pratama; Yansen Yansen (Universitas Budi Darma, 2022)
Technological developments in the modern era as it is today, there have been many innovations from scientists, communities and students to facilitate human activities. The results of this innovation are expected to help people's daily activities. However, there have not been many innovations that can facilitate human work, one of which is in the field of citizen services, such as the area of Rt 007 Rw 014 Kelurahan Pgilan, East Jakarta, which is currently trying to develop into a more developed and better area. The analytical method and technique used in this research is a SWOT analysis, by looking at the company's business needs and objectives. So the researcher aims to develop an Android-based application for the citizen service information system, because it will be very helpful in the citizen data storage system, as well as other citizen services directly in the citizen service application. And it can be directly accessed by the head of Rt 007. In making this Android-based application, the Java programming language is used as the Sharedpreferences database. With this citizen service application system, it is hoped that it will make it easier for the people of Rt 007 who are involved in data management and the head of Rt 007 or other management can monitor the application of citizen services